Thermodynamic Interaction between PAMAM G4-NH2, G4-OH, G3.5-COONa Dendrimers and Gemcitabine in Water Sotutions - Bartlomiej Palecz; Adam Buczkowski; Henryk Piekarski; Özge Kılınçarslan (International Journal of Secondary Metabolite)
The thermodynamics of complex formation of polyamideamine dendrimers: cationic PAMAM G4-NH2, neutral PAMAM G4-OH and anionic PAMAM G3.5-COONa with gemcitabine hydrochloride, an antitumor drug, in water at a temperature of 250C was studied. The investigations were carried out with the use of ITC measurements allowing one to determine the number of the drug molecules bonded by the dendrimer macromolecule, the equilibrium constants of the complex formed and the values of enthalpy and entropy of their formation. The measurements results obtained show different numbers of the drug molecules bonded by dendrimer macromolecules depending on the properties of their terminal groups.